Significance of the van der Waals force on the formation of the microstructure of wind-blown loess: An investigation using modified Discontinuous Deformation Analysis. (August 2022) - Li, Qiang; Li, Tonglu; Shen, Wei; Li, Hua; Li, Ping; Li, Yan; Hou, Xiaokun
Abstract: The van der Waals force is significant for the formation of microstructures of wind-blown deposits, such as loess soil. However, it is difficult to observe the effect of the van der Waals force in the natural environment and laboratory. The conventional DDA model, which simplifies contact as compressed elastic springs, has been successfully applied in simulating blocky rock behaviors, but it is incapable of simulating tension forces. In this paper, we modified the conventional DDA model by considering blocks as soil particles and by applying the van der Waals force among the particles to investigate the micro-behavior of fine soil. The modified DDA is validated by simulating two ideal experiments. Then, the falling process of fine grains (<65 μm), similar to wind-blown dust, is simulated by the modified and conventional DDA models separately. The simulated deposits of the falling grains by the two models show significant differences in microstructure. The microstructure generated by the modified DDA model is much closer to the loose structure of a real loess specimens, while that generated by the conventional DDA model is much more compact. This verifies that the van der Waals force is crucial for the formation of the loose microstructure of loess.